Helping Agritourism Visitors Learn During their Visits: AEC645/WC308, 6/2018 - Stofer, Kathryn A; Rumble, Joy N (EDIS, 2018)
Agritourism is a growing industry in Florida, and combines two of the state’s major assets: tourism and agriculture. This 4-page document outlines ways that agritourism operators can incorporate meaningful educational opportunities into their operation. Written by Kathryn Stofer and Joy N. Rumble and published by the UF/IFAS Department of Agricultural Education and Communication, June 2018. https://edis.ifas.ufl.edu/wc308